2011
DOI: 10.1111/j.1945-5100.2011.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotope fractionation and concentration measurements of Zn in meteorites determined by the double spike, IDMS‐TIMS techniques

Abstract: Abstract-The isotope fractionation of Zn in meteorites has been measured for the first time using thermal ionization mass spectrometry and a double spiking technique. The magnitude of dZn ranged from )0.29 to +0.38& amu )1 for five stone meteorites whereas the iron meteorite Canyon Diablo displays dZn of 1.11 ± 0.11& amu )1 . The results for chondrites in this work can be divided into positive and negative dZn, supporting a previous proposal that chondrites are a mixture of materials from two different tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
2
10
2
1
Order By: Relevance
“…As expected, all samples fall on a mass‐dependent fractionation line with a slope of 1.981 ( R 2 = 0.999) on the three‐isotope plot. In contradiction to Ghidan and Loss (), this study shows that Redfields' Zn isotopic composition is mass‐dependent just like any other bulk meteorite analyzed so far. The ranges of δ 66 Zn values significantly overlap for the different meteorite groups, with the isotopically heaviest sample being the IIE Watson (δ 66 Zn = 5.61‰) and the lightest being the III AB Casas Grandes (δ 66 Zn = −0.59‰ as measured by Luck et al.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…As expected, all samples fall on a mass‐dependent fractionation line with a slope of 1.981 ( R 2 = 0.999) on the three‐isotope plot. In contradiction to Ghidan and Loss (), this study shows that Redfields' Zn isotopic composition is mass‐dependent just like any other bulk meteorite analyzed so far. The ranges of δ 66 Zn values significantly overlap for the different meteorite groups, with the isotopically heaviest sample being the IIE Watson (δ 66 Zn = 5.61‰) and the lightest being the III AB Casas Grandes (δ 66 Zn = −0.59‰ as measured by Luck et al.…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, Zn isotopic fractionation in Redfields is totally mass‐dependent. Moreover, the Zn concentration of Redfields measured in this study (6.8 ppm) is very close to the isotope dilution measurement of Ghidan and Loss () (7.2 ppm) ensuring that our Zn purification technique is working correctly. The difference in isotopic compositions might be due to the heterogeneity of the samples or problem with measurement and data analysis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The average Zn fractionation for this group of HED meteorites was approximately zero, similar to ordinary chondrites (Luck et al, 2005;Moynier et al, 2007;Ghidan and Loss, 2011). Considering only the eucrite falls, the average d 66 Zn value of +0.50 ± 0.51& was identical to the CI chondrites reported by Luck et al (2005), who found mean d 66 Zn = +0.49& and +0.47& for Orgueil and Ivuna, respectively.…”
Section: Chondritic Origin For Vesta and The Origin Of The Elemental supporting
confidence: 66%
“…Zinc isotopic heterogeneity has been previously reported in chondrites and in iron meteorites by Luck et al (2005) and by Ghidan and Loss (2011). Ghosh and McSween (1998) proposed a model for Vesta of a melted center with an unmelted outer shell which would be expected to retain some isotopic heterogeneity.…”
Section: Isotopic Variation Within An Individual Meteoritementioning
confidence: 99%